A Proposed Curriculum For Teaching Arabic As A Third Language Based On The Common European Framework Of Reference CEFR At MARA University Of Technology/ تصور مقترح لمنهج تعليم اللغة العربية لغة ثالثة وفق معايير الإطار الأوروبي العام للغات بجامعة مارا للتكنولوجيا - Abdelhamid, Ibrahim Youssef; Hj. Mohd Yusop, Januddin Sardi; Mohamad Yusof, Mohd Akashah; Hassan, Lutfi; Haridy, Eman Ahmad; Yahaya, Hazrati (Ijaz Arabi Journal of Arabic Learning, 2025)
Arabic is being taught as a third language at MARA University of Technology in Malaysia for over ten thousand students every year. They learn to study the Arabic course at three levels designed by the curriculum writers. The present study is designed to provide a clear vision of the Arabic language curriculum as a third language at MARA University of Technology in Malaysia, based on The Common European Framework of Reference for Languages (CEFR) standards, to help those engaged in teaching Arabic at the university to develop an efficient Arabic language course based on CEFR. The researchers adopted the descriptive analytical approach to determine the realities of teaching and learning Arabic at the university and to adopt the CEFR standards to propose a curriculum for teaching Arabic as a third language at the MARA University of Technology. Researchers found that the Arabic language curriculum at Mara University of Technology needs to be redesigned by the Common European Framework of Reference for Languages CEFR. Therefore, The researchers proposed a curriculum for teaching Arabic as a third language based on the CEFR standards into two levels, Beginner A1 and Upper Beginner A2, appropriate for the MARA University of Technology's current Arabic language teaching situation. The researchers suggest that the officials in charge of teaching Arabic at the university use this proposed curriculum to develop the Arabic language course at the university. The researchers suggest for future work to design a curriculum for teaching Arabic at the intermediate and advanced levels according to the CEFR.